Great expectations - Dickens, Charles (London ; New York : Oxford Univ. Press, 1978)
An unknown person has provided money for the education of a poor English boy, in eighteenth-century England.
Wilson's Fiction.
Wilson's Senior High School.
7.1.
7.1
Young Adult
Keywords: Great Britain -- Fiction; Great Britain -- Fiction